Utility Of Blood Indices And Parameters For Differentiating Iron Deficiency Anaemia And Β-Thalassemia Trait By Calculating Various Discriminant Functions (Indian Journal of Applied-Basic Medical Sciences, 2020)
Background: There are various causes of hypochromic microcytic anaemia. Among these  β-thalassemia trait and iron deficiency anaemia are much more common in developing  country like India. Various parameters obtained on automated haematology analyser by  calculating discriminant functions to differentiate iron deficiency anaemia and β thalassemia trait becomes easy and cost effective.  Objective: To differentiate iron deficiency anaemia and β-thalassemia trait by blood indices,  red cell distribution width and various discriminant functions.  Materials and Methods: This study was carried out in the pathology department of AMC  MET medical college, L.G.Hospital, Maninagar, Ahmedabad. We had studied 100 cases of  differentiating Iron deficiency Anaemia and β-Thalassaemia trait from patient’s case records  and laboratory reports irrespective of age and sex over a period of one year (January 2019  to December 2019). Tests for serum iron and ferritin were carried out in individuals showing  low hemoglobin (Hb). All the selected subjects’ samples were subjected to blood  morphology, comparison of MCV, RBC count, RDW, RDWI, SI, GI and MI. Results: Out of 100 cases seventy five were diagnosed having IDA, whereas twenty five were  having β-TT. The RBC count was higher, and MCV was much lower in βTT as compared to  IDA. Both groups were subjected to RDW,RDWI, SI, MI and GI. Conclusion: Among various discriminant function calculated from different haematological  parameters and blood indices Mentzer index and Srivasta index are more sensitive and  specific for differentiating IDA and β-TT.
Keywords: β-Thalassemia trait; Iron deficiency anaemia; Red Cell Distribution Width Index (RDWI); Mentzer Index; Srivasta index; Green and king Index